Rare Earth Elements abundance, fractionation, and anomalies in the sediments of the Cananéia-Iguape Estuarine-Lagoon Complex in Brazil - Vitor G. Chiozzini; Deborah I. T. Fávaro; Elisabete S. Braga (Ocean and Coastal Research)
The Cananéia-Iguape Estuarine-Lagoon Complex (CIELC) is an extremely productive coastal ecosystem. It encloses the Valo Grande channel, built 160 years ago, which introduces water from the Ribeira River directly into the estuarine system, contributing to important biogeochemical changes in the region. Many nutrients arrive at the estuary through this channel, as well as metals and other slightly soluble elements that become part of the sediments. This study aims to evaluate the processes that govern the distribution of rare earth elements (REE) in the sediments of the complex by using fractionation patterns, anomalies, and the geochemical signature of minerals to evaluate sources, natural levels, and the possible anthropogenic forcing to which CIELC is subjected. ∑REE* ranged from 14.2 to 285 mg kg-1 and showed a distribution related to depositional/textural characteristics influenced by the regional and local lithological setting and a possible contamination. The REE/Al ratio indicated enrichment in the sea adjacent to the estuary and at stations in the Ribeira River and Valo Grande. While the Hf/Al ratio indicated natural enrichment related to the presence of heavy minerals in most of these stations, this ratio fails to justify enrichment at some stations in the northern part of the estuary and the Ribeira River. Fractionation patterns and anomalies allowed us to identify the main heavy minerals related to REE enrichment at CIELC. Cerium (Ce) anomalies showed a possible relation with biologically mediated Ce+3 to Ce+4 oxidation processes in the most productive areas of the estuary. Europium (Eu) anomalies were strongly associated with different mineral assemblies in several CIELC sectors. Abundance, fractionation patterns, and REE anomalies corroborate the categorization of CIELC sediments as part of a pristine system in its southern region and as subject to anthropogenic influences in its northern area.